2022
DOI: 10.1016/j.eclinm.2021.101219
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation needs following COVID-19: Five-month post-discharge clinical follow-up of individuals with concerning self-reported symptoms

Abstract: Background This report describes and objectivizes reported problems among a cohort of previously hospitalized COVID-19 patients by clinical examination and determination of the required level of rehabilitation sevices. Methods This report forms part of the Linköping COVID-19 Study (LinCoS) that included 745 individuals from one of 21 Swedish healthcare regions, Region Östergötland (RÖ), admitted to hospital for COVID-19 during March 1st–May 31st, 2020. In this descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 44 publications
3
39
0
4
Order By: Relevance
“…The results of this study suggest that many COVID-19 survivors have a long-term psychical impairment. A cohort study in Sweden reported that one out of five inpatients required rehabilitation intervention even five months after discharge [ 54 ]. These findings indicate that the next direction should be building a system that provides rehabilitation interventions to an unprecedented number of people suffering physical impairments, such as post-COVID conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that many COVID-19 survivors have a long-term psychical impairment. A cohort study in Sweden reported that one out of five inpatients required rehabilitation intervention even five months after discharge [ 54 ]. These findings indicate that the next direction should be building a system that provides rehabilitation interventions to an unprecedented number of people suffering physical impairments, such as post-COVID conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 26 One study showed that nociceptive-type pain was considerably more common than neuropathic-type pain. 29 Another study reported that the most common regional areas for arthralgia are knee joint, ankle joint and shoulder joint, while the most common areas for myalgia are lower leg, arm, and shoulder girdle. 30 …”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Bei entsprechender Schwere und häufiger auch sehr langer Persistenz über die akute Krankenhausbehandlung hinaus [18] bedürfen sie einer spezifischen neurorehabilitativen Behandlung mit neurologischer Frührehabilitation und/oder Anschlussrehabilitation, ggf. auch erneut im weiteren Verlauf [19].…”
Section: Dasunclassified
“…Da Schädigungen des peripheren und zentralen Nervensystems eine gute Chance auf funktionelle Erholung bei adäquater Neurorehabilitationsbehandlung haben, dafür aber häufiger eine längere Behandlung erforderlich ist, ist der Rehabilitationsbedarf bei Long-COVID/Post-COVID mit neurologischer Manifestation teilweise über eine längere Zeit erforderlich bzw. wiederholt zu prüfen, um dem individuellen Bedarf gerecht zu werden [19].…”
Section: Neurologische Rehabilitation Bei Covid-19unclassified